Золоті вінки — нагороди ольвіополітів - Скржинська, М.В. (Археологія, 2002)
Статтю присвячено аналізу 28 ольвійських написів із згадками про нагородження золотими вінками. Автор встановлює, хто і за віщо одержував вінок і де проходила церемонія нагородження. Ольвийские надписи с упоминанием о наградах золотыми венками намного превосходят надписи из других городов Северного Причерноморья как по количеству, так и по характеру сообщений об обстоятельствах награждения. В статье исследованы 28 ольвийских надписей III в. до н. э. — III в. н. э. Золотые венки получали соотечественники и иностранцы за особые заслуги перед государством, таким способом чтили также некоторых умерших ольвиополитов. В некоторых случаях, особенно в римское время, государство издавало лишь почетный декрет, а венок приобретали награжденные или их друзья и родственники. В IV—I вв. до н. э. венчание золотым венком проходило на крупнейших ольвийских празднествах — Дионисиях в театре и во время игр в честь Ахилла на Тендровской косе; почетные декреты читали также в Народном собрании, а в римский период там проходила и церемония награждения. Некоторые граждане Ольвии получали подобные награды в других греческих городах. Оlbian inscriptions with the mentions of awarding with golden garlands excel the inscriptions from the other cities of the northern Black Sea area in their quantity as well as in the character of information about the circumstances of awarding. 28 Olbian inscriptions of the III century BC — III century AD have been analyzed in the article. Golden garlands were given to the compatriots as well as to the foreigners for their outstanding services to the state. Some dead Olbiopolites were also honored in this way. In a number of cases, especially in Roman times, the state only published the honorary decree, and the awarded people or their friends or relatives bought the garlands. In the IV — I centuries BC the coronation with the golden garland took place at the main Olbian holidays — Dionysia in the theaters and during the games in honor of Achilles on the Tendrovskaya spit, the honorary decrees were read also at the People’s meetings and during the Roman period the ceremony of awarding also took place there. Some Olbjan citizens got such awards also in the other Greek cities.